Introducing Motor Games to Improve Physical Health and Coordination in Elementary School Students - Hilmy Aliriad; Wahyu Setia Kuscahyaning Putri; Olivia Dwi Cahyani; Mohamad Da'i; Miftahul Hidayat; Juwita Isna Salsa Bella (Jurnal Panjar: Pengabdian Bidang Pembelajaran, 2026)
Sedentary lifestyles and conventional physical education limit the motor development of primary school children. This community service program aimed to improve the physical health and movement coordination of pupils at MI ICP Nurul Ulum Bojonegoro through the introduction of creative, enjoyable, and educational motor games. The program applied a participatory and educational approach across five stages, namely socialization, teacher training, technology and innovation adoption, mentoring and evaluation, and program sustainability. The core innovation was the Interactive Motor Learning Innovation Package (PIMI), which combines simple physical equipment with QR code video tutorials and a Merdeka Curriculum based motor game module. Up to the midpoint of implementation, the team completed initial coordination, socialization and the formation of a healthy school team, teacher training, module preparation, equipment procurement, and most field mentoring. Preliminary results show high student enthusiasm, improved teacher capacity in designing motor activities, and the emergence of more varied physical activity habits. The program demonstrates that an accessible and low-cost technology can be absorbed independently by partner teachers and holds strong potential to be replicated as a model of a healthy, game-based school in Bojonegoro.